2017
DOI: 10.1016/j.ejor.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate dependence and portfolio optimization algorithms under illiquid market scenarios

Abstract: We propose a model for optimizing structured portfolios with liquidity-adjusted Value-at-Risk (LVaR) constraints, whereby linear correlations between assets are replaced by the multivariate nonlinear dependence structure based on Dynamic Conditional Correlation t-copula modeling. Our portfolio optimization algorithm minimizes the LVaR function under adverse market circumstances and multiple operational and financial constraints. When we consider a diversified portfolio of international stock and commodity mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 54 publications
8
53
0
1
Order By: Relevance
“…In addition, the effect of liquidity risks on VaR also needs to be accounted for, because of the illiquid scenarios under market turmoil and crises. Several works have developed liquidity‐adjusted VaR models (e.g., Al Janabi, Hernandez, Berger, & Nguyen, ; Berkowitz, ; Weiß & Supper, ). Al Janabi et al (), for instance, propose a model to optimize structured portfolios with liquidity‐adjusted VaR, while taking into account the nonlinear dependence structure among portfolio assets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the effect of liquidity risks on VaR also needs to be accounted for, because of the illiquid scenarios under market turmoil and crises. Several works have developed liquidity‐adjusted VaR models (e.g., Al Janabi, Hernandez, Berger, & Nguyen, ; Berkowitz, ; Weiß & Supper, ). Al Janabi et al (), for instance, propose a model to optimize structured portfolios with liquidity‐adjusted VaR, while taking into account the nonlinear dependence structure among portfolio assets.…”
Section: Resultsmentioning
confidence: 99%
“…Several works have developed liquidity‐adjusted VaR models (e.g., Al Janabi, Hernandez, Berger, & Nguyen, ; Berkowitz, ; Weiß & Supper, ). Al Janabi et al (), for instance, propose a model to optimize structured portfolios with liquidity‐adjusted VaR, while taking into account the nonlinear dependence structure among portfolio assets. They show evidence of the superiority of their models over the competing portfolio strategies including the minimum variance, risk parity and equally weighted portfolio allocations.…”
Section: Resultsmentioning
confidence: 99%
“…These empirical findings have important implications to portfolio management practices and may appeal to risk managers, portfolio managers and regulatory agencies in wake of the repercussions of the 2007-2009 GFC. Portfolio managers are increasingly interested in managing liquidity risk, specifically the downside risk associated with liquidity exposure (e.g., Al Janabi et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent papers in quantitative and mathematical finance have shown that copula models are flexible enough for modelling nonlinear dependence and tail risk (e.g. Al Janabi, Arreola Hernandez, Berger, & Nguyen, 2017; Grundke & Polle, 2012; Irresberger, Wei, & Gabrysch, 2018). When fitting copula functions, we particularly suggest a special forcing variable to better model the dependence parameter of the 90° rotated Clayton and 270° rotated Clayton copulas.…”
Section: Introductionmentioning
confidence: 99%